Impact of Anesthesia Type on Stone Clearance and Morbidity in Ureteroscopy: General Versus Spinal Anesthesia: Impact of Anesthesia Type on Stone Clearance and Morbidity - Iqbal, Atif; Saeed, Syeda Javeriya; Liaqat, Khurram; Ovais, Fatima; Qamber, Jawad Hussain; Nadia, Sarah (Pakistan Journal of Health Sciences, 2025)
Anaesthesiologists prefer regional anesthesia for ureterorenoscopy to prevent difficulties after the procedure, whereas surgeons prefer general anesthesia in order to prevent ureteral damage. However, limited comparative data exist regarding the outcomes of these anesthesia techniques in ureteroscopy-assisted stone clearance Objective: To compare spinal and general anesthesia regarding efficacy, safety, and patient outcomes during ureteroscopy for ureteric stones. Methods: This quasi-experimental study included 90 patients aged between 20-60 years in total were chosen. Using a semi-rigid ureteroscope (8/8.4 fr), all individuals had ureteroscopic treatment for ureteric stones. Equal numbers of 45 patients were divided between the two groups. General anesthesia was administered to Group A, and spinal anesthesia was provided to Group B. The participants’ demographic data, hospital stays, operating times, stone removal rates, and intra- and post-operative problems were all recorded. Data on intraoperative parameters, stone clearance, and postoperative complications were collected and analysed using SPSS 23.0. Results: General anesthesia significantly reduced the dilatation time (104.01 ± 12.772 vs. 130.552 ± 22.532 sec, p < 0.001) and time to reach the stone (126.68 ± 12.592 vs. 137.602 ± 17.841 sec, p < 0.001) compared to spinal anesthesia. However, no significant differences were observed in lithotripsy time, operation time, stone-free rates, or postoperative complications between the two groups. Patients in the GA group reported higher VAS scores and an increased frequency of nausea/vomiting after surgery. Conclusion: General anesthesia reduced the time for dilatation and stone access but showed no significant advantages in lithotripsy time, operation time, stone-free rates, or complications.